2005
DOI: 10.4049/jimmunol.174.11.7006
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-Producing CD4+CD25+ Regulatory T Cells Play a Critical Role in Granulocyte-Macrophage Colony-Stimulating Factor-Induced Suppression of Experimental Autoimmune Thyroiditis

Abstract: Our earlier study showed that GM-CSF has the potential not only to prevent, but also to suppress, experimental autoimmune thyroiditis (EAT). GM-CSF-induced EAT suppression in mice was accompanied by an increase in the frequency of CD4+CD25+ regulatory T cells that could suppress mouse thyroglobulin (mTg)-specific T cell responses in vitro, but the underlying mechanism of this suppression was not elucidated. In this study we show that GM-CSF can induce dendritic cells (DCs) with a semimature phenotype, an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
102
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 55 publications
14
102
1
1
Order By: Relevance
“…Th2 cells induce production of IgA, IgE, and IgG subclasses that do not fix complement and produce anti-inflammatory cytokines, which may down-modulate immune responses, possibly by acting as growth and differentiation factors for Tregs (34,35). Similar to previous findings (10,11,38) in the T cell-mediated disease experimental autoimmune thyroiditis (EAT), we have shown that treatment with GM-CSF results in mobilization of CD11c Ï© /CD8␣ ÏȘ DCs and a skewing of the immune response to a Th2 polarization in the EAMG mouse model. Accordingly, GM-CSF-treated mice showed only slight increases in the intracellular expression of IFN-␄ and TNF-␣ by splenocytes compared with nonimmunized control (CFA) mice, had significantly reduced levels of these cytokines, and increased production of IL-4 and IL-10 compared with control tAChR-immunized mice.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Th2 cells induce production of IgA, IgE, and IgG subclasses that do not fix complement and produce anti-inflammatory cytokines, which may down-modulate immune responses, possibly by acting as growth and differentiation factors for Tregs (34,35). Similar to previous findings (10,11,38) in the T cell-mediated disease experimental autoimmune thyroiditis (EAT), we have shown that treatment with GM-CSF results in mobilization of CD11c Ï© /CD8␣ ÏȘ DCs and a skewing of the immune response to a Th2 polarization in the EAMG mouse model. Accordingly, GM-CSF-treated mice showed only slight increases in the intracellular expression of IFN-␄ and TNF-␣ by splenocytes compared with nonimmunized control (CFA) mice, had significantly reduced levels of these cytokines, and increased production of IL-4 and IL-10 compared with control tAChR-immunized mice.…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, the administration of GM-CSF was recently shown to suppress a T cell-mediated autoimmune disease, experimental autoimmune thyroiditis, while administration of fms-like tyrosine kinase receptor 3-ligand (Flt3-L) had opposite effects (10). The observed suppression associated with GM-CSF treatment was dependent upon the presence of IL-10-producing CD4 Ï© CD25 Ï© Tregs induced by tolerogenic DCs (11).…”
Section: A Utoimmune Myasthenia Gravis (Mg)mentioning
confidence: 99%
“…+ Tregs is increased in ACAID mice CD4 + CD25 + T cells have been shown to play a critical role in immune tolerance and immune responses in various diseases and experimental models of disease in rodents and humans [5,7,12]. Our study aimed to examine whether CD4 + CD25 + T cells were increased in ACAID, an eyederived immune tolerance model.…”
Section: Frequency Of Splenic Cd4mentioning
confidence: 99%
“…Tregs are kept at a basal state of activation by low levels of circulating auto-antigen; the homeostatic level is sufficient to prevent the development of autoimmunity, but the clonal balance between Tregs and auto-reactive T cells could be overcome by immunogenic stimuli, such as the administration of mTG and adjuvant. [21][22] As demonstrated by the group of Prabnakar, 23 In addition to cell-mediated immune mechanisms, AITD is characterized by the secretion of antibodies(Abs) to a variety of thyroid-specific antigens, most notably thyroglobulin(Tg), and thyroid peroxidase(TPO) but also to a lesser extent the TSH receptor, the sodium iodide symporter(NIS), and most recently pendrin. 13,14 Experimental evidence in mice demonstrated that, apart from Tg, TPO is also a major antigen in chronic autoimmune thyroiditis.…”
Section: Basic Mechanisms In the Development Of Thyroid Autoimmunitymentioning
confidence: 99%